Increasing the Students’ Reading Comprehension Achievement Through Retelling Stories Technique at the Eighth-Grade Students - Gulo, Yaniria; Pangaribuan, Jontra Jusat; Tarigan, Karisma Erikson (English Lecturers and Teachers Association (ELTA), 2025)
This research was conducted to increase reading comprehension through the retelling stories technique among the eighth-grade students’ of SMP Swasta Primbana. In conducting research this research, the writer used Classroom Action Research (CAR). This research showed that teaching reading through retelling stories to the eighth-grade students’ of SMP Swasta Primbana could improve their reading. The result of the research showed that the students’ responses after being taught by using the retelling stories technique were good. The result of the test showed that the students’ mean score on the pre-test was 58,75, on the formative test the students’ mean score was 68,03, and on the post-test, the student's mean score was 81,42. The research, findings showed that using retelling stories techniques could improve reading comprehension achievement. It is advisable that English teachers apply Retelling Stories Technique in order to improve reading comprehension. Keywords : Retelling Stories, Reading, Descriptive Test